COVID-19 and the Need for Innovation in International Education: Universidad San Francisco de Quito USFQ Case Study (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
The value of international education lies in facilitating meaningful cultural immersion as a catalyst for intercultural learning and the creation of global citizens. As the current pandemic poses a threat to the survival of international education offices across the globe, Institutions of Higher Education (IHEs) are facing not only unprecedented challenges, but also opportunities to strengthen students' capacity to address the issues of the 21st century. This essay will include a brief case study and address the importance of innovation in international education given the current pandemic.